Reconfigurable electrical interconnection strategies for photovoltaic arrays: A review - La Manna, Damiano; Li Vigni, Vincenzo; Riva Sanseverino, Eleonora; Di Dio, Vincenzo; Romano, Pietro (Renewable & sustainable energy reviews, 2014)
Non-uniform irradiance significantly decreases the power delivered by solar photovoltaic arrays. A promising technique for compensating these power losses relies on dynamically reconfiguring the electrical connections between photovoltaic modules. This paper presents the current state-of-the-art strategies for photovoltaic array reconfiguration in order to increase the power output under partial shading and mismatch conditions. The different approaches have been compared in terms of effectiveness of the control algorithms, monitored electrical and environmental variables, overall hardware complexity and specific features of each solution. Finally, the most challenging aspects of the reconfiguration strategy are identified and further discussed.